RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND ENGLISH TEACHING EFFECTIVENESS IN PRIVATE COLLEGES (Contemporary Journal of Social Science Review, 2025)
The present study responds to the significant research gap concerning the effects of teaching effectiveness (TE) on emotional intelligence (EI) among English as Foreign Language (EFL) teachers, especially in the context of the Pakistani private colleges. Although there is a lot of current literature on EI within the educational circles, little was known particularly about EI and its association with the effectiveness of teaching EFL in a non-western context. Informing such professional growth of language educators, it is essential to understand this relationship so that it could be used to enhance the specific teaching methodologies. The main purpose of the research was to review the predicting power of the various dimensions of EI in the context of EFL teachers in predicting TE, and investigate how teacher’s qualifications and experience influence their EI and TE. The research design adopted was a quantitative research design where 100 teachers of EFL (private colleges) in Okara, Pakistan were used. The Bar-On Emotional Quotient Inventory (EQ-i) was used to gather data related to EI and Characteristics of Effective English Language Teacher (CEELT) questionnaire on TE. A data analysis was conducted with descriptive statistics, Pearson correlation analysis, multiple regression, ANOVA, and t-tests. The findings revealed that both Intrapersonal EI (Beta = 0.38, p < 0.001) and Interpersonal EI (Beta = 0.36, p < 0.001) were the most significant predictors of TE; however, the first demonstrated the strongest prediction of TE, i.e., 0.76 of the variance in TE was explained (R 2 = 0.76). The means differences between teaching experience and qualification were found significant in both good and bad EI, TE where teachers with Doctorate/PhD and with over 5 years of experience showed significant higher scores and points on EI and TE (p < 0.05). The study adds value to the literature by empirically supporting the role of EI in improving the teaching effectiveness of EFL teaching especially in a non-Western learning environment and the significance of EI centered professional development as it relates to teaching outcomes.